1973
DOI: 10.1159/000240621
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Enzyme Development for Glycerol Utilization by Neonatal Rat Liver

Abstract: Glycerol kinase and glycerol 3-phosphate dehydrogenase activities have been measured in perinatal rat liver. Hydrocortisone stimulates the activity of glycerol 3-phosphate dehydrogenase and thyroxine and hydrocortisone stimulate glycerol kinase activity in the fetal liver. The postnatal increase in the activity of both enzymes is prevented by starvation and can be restored by injection of glycerol. Glycerol is also effective in increasing the fetal liver activity of glycerol kinase. The role of glycerol in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1976
1976
1992
1992

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…In addition, this increase was correlated with the increase in glycerol kinase activity. Similar observations of an increase in enzymes of glycerol metabolism in the liver after birth were reported by other investigators (36,37). Quantitatively, in the 0-to 4-d-old newborn dogs, Hall et al (38) reported that approximately 50% of glycerol carbon was converted to glucose, accounting for 14% of glucose carbon.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, this increase was correlated with the increase in glycerol kinase activity. Similar observations of an increase in enzymes of glycerol metabolism in the liver after birth were reported by other investigators (36,37). Quantitatively, in the 0-to 4-d-old newborn dogs, Hall et al (38) reported that approximately 50% of glycerol carbon was converted to glucose, accounting for 14% of glucose carbon.…”
Section: Discussionsupporting
confidence: 77%
“…Mixing experiments showed that the low fetal activities were probably not due to an inhibitor. The rise in cGPDH in early extrauterine life is compa rable to that previously reported for rats [30], where the enzyme is apparently under hormonal control [32], To begin an investi gation of the possibility of different fetal and adult forms of cGPDH, we analyzed the kinetic properties of the enzyme in both of its catalytic directions. Our data (table IV) were similar to those reported for adult beef [7] and human [10] liver and showed no dif ference between the fetal and infant activi ties.…”
Section: Discussionsupporting
confidence: 52%
“…In the rat fetus, glycerol metabolism in creases late in gestation and during the first weeks of extrauterine life [30,32]. These increases are correlated with increases in the activities of liver GK and cGPDH [24,30], possibly stimulated by thyroid hormones [18,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation